2020
DOI: 10.7202/1073530ar
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmes des médecins traitants lors du retour au travail de personnes aux prises avec un trouble mental courant : illustration par des vignettes cliniques

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit. Érudit est un consortium interuniversitaire sans but lucratif composé de l'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…33 Other factors that may explain these suboptimal practices include the lack of time available during consultations and physicians' fee-for-service remuneration models, which can limit physicians' level of engagement in the management of their patients' mental health-related sick leave. 13,15,34 Second, we found that access to mental health-related sick leave services varied in function of the level of involvement of different stakeholders and professionals. As mentioned by Corbière et al, 30 even if all stakeholders share the interest of achieving safe and sustainable return to work, the collaboration between them is difficult because each stakeholders' role are not well defined and understood by everyone.…”
Section: The Match Between the Person's Needs And Their Ability To Ac...mentioning
confidence: 90%
See 4 more Smart Citations
“…33 Other factors that may explain these suboptimal practices include the lack of time available during consultations and physicians' fee-for-service remuneration models, which can limit physicians' level of engagement in the management of their patients' mental health-related sick leave. 13,15,34 Second, we found that access to mental health-related sick leave services varied in function of the level of involvement of different stakeholders and professionals. As mentioned by Corbière et al, 30 even if all stakeholders share the interest of achieving safe and sustainable return to work, the collaboration between them is difficult because each stakeholders' role are not well defined and understood by everyone.…”
Section: The Match Between the Person's Needs And Their Ability To Ac...mentioning
confidence: 90%
“…For example, this has been raised in a recent Swedish study, aimed at documenting organizational factors influencing return‐to‐work coordination processes, which found that lack of collaboration, long waiting times and inadequate drawing of RTW plans by primary care physicians were perceived as main barriers to better RTW coordination 33 . Other factors that may explain these suboptimal practices include the lack of time available during consultations and physicians' fee‐for‐service remuneration models, which can limit physicians' level of engagement in the management of their patients' mental health‐related sick leave 13,15,34 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations